THE ANALYSIS OF SEMANTIC MEANING FOUND IN COMMENTS OF CINTA LAURA’S INSTAGRAM ACCOUNT CLAURAKIEHL - quanita putri, ragil (Lingustic, Literature and English Education, 2025)
This research aims to analyze the types of semantic meaning found in the comments section of Cinta Laura’s Instagram account (@claurakiehl). The study uses a descriptive qualitative method to identify and classify comments based on Geoffrey Leech’s (1981) theory of seven types of meaning; conceptual, connotative, social, affective, reflected, collocative, and thematic. A total of 516 English-language comments collected from eleven posts made in April 2025 were analyzed. The findings reveal that all seven types of meaning appear, with Affective Meaning being the most dominant (44%), followed by Conceptual Meaning (20.9%) and Connotative Meaning (18%). The results indicate that Instagram comments serve as expressive linguistic media that reflect emotional engagement, social relationships, and symbolic interpretation. This study contributes to the understanding of semantic meaning in digital communication contexts and demonstrates the role of language in expressing identity and emotion on social media.